The Role of Hearing Aids in Improving Dual‐Task Gait Performance in Older Adults With Presbycusis: A Cognitive and Motor Analysis - Soylemez, Emre; Soylemez, Tugce Gurel; Apaydin, Aydin Sinan; Apaydin, Zuhal Koc; Yasar, Murat (Wiley, 2024)
ABSTRACTBackgroundCognitive decline is a common challenge faced by older individuals with presbycusis; their performance on dual‐task (DT) activities is generally lower compared to those without hearing loss. However, the influence of hearing aids on nonauditory cognitive decline in this population remains unclear. This study aims to investigate the effect of hearing aids on nonauditory DT performance in older adults with presbycusis.Material and MethodsThis study included older people with presbycusis who used hearing aids (P&HA group), those with presbycusis who did not use hearing aids (PoHA group), and a control group of healthy adults. Forward and backward digit span tests and timed up and go test (TUG) were administered to all individuals. TUG and motor and cognitive (forward and backward digit span) tasks were applied simultaneously to evaluate the participants' DT performance.ResultsThe study comprised 60 individuals with presbycusis (19 females, 41 males; mean age: 73.23 ± 6.49 years) and 30 healthy adults (15 females, 15 males; mean age: 35.93 ± 8.57 years). Healthy adults performed better than the P&HA and PoHA groups in all the administered tests (p < 0.05). There was a moderate negative relationship between the severity of hearing loss and the forward and backward digit span test performances (p < 0.05). The P&HA group performed better than the PoHA group on the DT cognitive forward and backward digit span tests.ConclusionThe use of hearing aids and their proper fitting are important not only for improving communication skills and reducing listening effort but also for supporting nonauditory cognitive functions, minimizing the risk of falls during DT activities, and enhancing the overall quality of life.
Keywords: Male; Adult; Aged, 80 and over; Neurosciences. Biological psychiatry. Neuropsychiatry; Presbycusis; Middle Aged; hearing aids; working memory; Hearing Aids; Cognition; Humans; dual task; Original Article; Female; Cognitive Dysfunction; presbycusis; Gait; Psychomotor Performance; hearing loss; RC321-571; Aged